2018
DOI: 10.1111/wrr.12663
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ prediction of their wound healing time

Abstract: Understanding and managing patients' expectations can help improve their adherence to treatment for chronic wounds; however, little is known concerning about their expectations regarding healing time. Recruited subjects were asked to predict how long their wounds would take to heal and their charts were reviewed to retrieve real time of healing. We recruited 100 subjects from which 77% have healed. Fifty-three subjects (68.8%) had a longer healing time than they predicted (underestimated), and 17 (22.1%) had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The healing rates of chronic wounds range between 36% and 60% 47 ; however, Borda et al showed a higher rate (77%) of wound healing in a population with predominantly higher level of education (college education or higher) and concluding that patients with a lower level of education would be prone to misunderstand the instructions given by the provider, leading to a longer time to heal. 48…”
Section: Discussionmentioning
confidence: 99%
“…The healing rates of chronic wounds range between 36% and 60% 47 ; however, Borda et al showed a higher rate (77%) of wound healing in a population with predominantly higher level of education (college education or higher) and concluding that patients with a lower level of education would be prone to misunderstand the instructions given by the provider, leading to a longer time to heal. 48…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the possibility of wound healing is related to wound duration. The possibility of successfully healing the wound will significantly reduce with the extension of the time of wound appearance, which will increase the difficulty of wound healing (Borda et al, 2018). Therefore, the demand for wound treatment and care is increasing.…”
Section: Introductionmentioning
confidence: 99%